Intrahepatic Cholestasis of Pregnancy: Natural History and Current Management - Roediger, Rebecca; Fleckenstein, Jaquelyn (Seminars in Liver Disease, 2021)
Intrahepatic cholestasis of pregnancy (ICP) is a common disorder in the second half of pregnancy characterized by pruritus and elevated serum bile acids (BAs) with spontaneous resolution after delivery. ICP carries a risk of adverse effects on the fetus which correlates with the degree of BA elevation. ICP occurs in genetically susceptible women as the reproductive hormones increase during pregnancy. Ursodeoxycholic acid is still considered the first-line treatment for ICP though it is of unproven benefit in preventing adverse effects on the fetus. Fetal complications, such as stillbirth, increase with gestational age, so preterm delivery is generally performed in cases of severe ICP, defined as BA levels above 40 μmol/L. ICP may recur in future pregnancies and is associated with an increased risk for future hepatobiliary, immune mediated, and cardiovascular diseases. Children born of mothers with ICP have normal development but may have a risk for subsequent metabolic disease.
Keywords: cholestasis; pregnancy; pruritus